The Effect of Tax Aggressiveness on Financial Performance Moderated by Bonded Zone Facilities - Ferdinand Agustinus; Andang Wirawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In an increasingly competitive business world, companies are required to optimize their performance, including in financial aspects. One of the strategies carried out by companies to increase financial efficiency is by conducting tax aggressiveness, namely legal and illegal efforts to minimize tax burdens. However, tax aggressiveness can have a negative impact on the company's reputation and sustainability. This study aims to determine the effect of tax aggressiveness on financial performance moderated by bonded zone facilities. This type of research was conducted using a quantitative approach. The types and sources of data collected were secondary data. The data collection techniques used were documentation techniques and literature studies. The data analysis used in this study was statistical analysis of SPSS (Statistic Package for Social Science) version 29. The data analysis method used in this study was simple linear regression analysis. The results of the study showed that tax aggressiveness had a positive effect on the company's financial performance, which was reflected in the increase in ROA and ROE. In addition, bonded zone facilities (KB) can moderate (weaken) the effect of tax aggressiveness on the company's financial performance, which was reflected in ROA and ROE.